The Exploration of Islamic Educational Reform and Colonialism Impact on Contemporary Islamic Higher Education - Mariam Ulpah (Khazanah Pendidikan Islam, 2022)
Many historians and scholars have embraced the concept of ""tradition vs modernity,"" arguing that Islamic educational institutions play a minor role in Muslim civilization's intellectual development. Despite the fact that portrayals of Islamic educational institutions, such as madrasas, as legacies of medieval antiquity are still popular in public discourse, numerous historians, philosophers, and scholars have debated this concept over the years. This research is a comparative study to explore the modern Islamic educational reform in Islamic higher education in Tunisia and Indonesia. As well as its contribution to development. The purpose of this study is to answer what are the explorations of educational reform in Indonesia and Tunisia's higher education? What is both countries' contribution to the development of Islamic education? The study was conducted using a qualitative method with an historical approach. The historical books of colonialism in Indonesia and Tunisia were used to collect data for the exploration of Islamic educational reform in Islamic higher education. Data also includes journals, articles, books, news, and international data that are relevant to the theme. The findings of the study show that modern reform is impacted by the colonial system in Indonesia, which allowed faith-based schools to take control of the schools. Islamic higher education in Indonesia is growing with modern ideas and has a dualistic system. While in Tunisia, of the French colonial type, they tried to get rid of all Islamic education because many Islamic higher education or madrasas were gotten rid of. As a result, following the end of colonialism, Islamic higher education in Tunisia now consists of just one and only Zaitunah University as part of Islamic civilization. This paper expects that by providing insight into colonial-era transformations, current and future generations of educators will recognize their significance and help to reintegrate an Islamic worldview, epistemology, and ethics into higher education development.